URGENSI PEMELIHARAAN DAN PERAWATAN SARANA DAN PRASARANA PENDIDIKAN PERSPEKTIF ISLAM - Siti Istiqlaliyah (JIEM: Journal of Islamic Education and Manajemen, 2021)
Maintenance and maintenance of educational facilities and infrastructure is an activity to carry out the management and arrangement of facilities and infrastructure so that it is always in good condition and ready for use in achieving educational goals. Maintenance and maintenance of facilities and infrastructure has been regulated in QS. Al-Maidah verse 32 indirectly provides the understanding that if the education wants to progress, be clever in maintaining and maintaining goods or facilities and infrastructure remain durable, and that can save costs. Maintenance and maintenance of educational facilities and infrastructure, especially those that require special care, are needed by people who have expertise in the field of care. In this maintenance and care, it is also necessary to have an attitude of mutuality even though the facilities and infrastructure are facilities in general, but we must use them like our own.